Evaluation of carcass merit pricing by pork packers - Schroeder, Ted C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Live hog prices must reflect end-use value to convey market information from consumers to producers. Precise end-use value is excessively costly to trace for each carcass given current technology. Pricing structures must be based upon carcass merit information that is correlated with end-use value. This study uses pork carcass cut out data from 794 carcasses to estimate hog carcass values based upon carcass characteristics. Carcass values varied by nearly $20/cwt based on quality differences alone. In addition, considerable differences were present in pricing schedules of different pork packers suggesting that hog producers need to shop around when deciding to which packer they sell their hogs.
Keywords: Swine; Hog carcass merit pricing; Pork pricing systems; Packer pricing